The Influence of Nano Titanium as Bitumen Modifier in Stone Mastic Asphalt - Khairil Azman Masri; Nur Syafiqah Shamimi Mohd Zali; Ramadhansyah Putra Jaya; Mazlan Abu Seman; Mohd Rosli Mohd Hasan (Advances in Materials Science and Engineering)
Nanomaterials are emerging as one of the methods to improve the pavement industry. Due to that, this study explores the influence of nano TiO2 modified binder and mixture with 60/70 grade bitumen. The first stage discovers the physical properties of bitumen by undergoing penetration and softening point tests. Then, the nano TiO2 modified binder is evaluated in terms of its morphological and chemical properties. To verify the modified binder design, the mechanical performance of stone mastic asphalt (SMA) is assessed in terms of volumetric properties. From the results, 5% nano TiO2 modified binder shows significant improvement in terms of penetration and softening point. The results also show that the 3% nano TiO2 modified binder contributes the highest improvement in terms of its chemical properties and the morphological properties. Based on the morphological properties’ evaluation, FTIR and XRD observed a sharp peak of nano TiO2 while the bitumen containing nano TiO2 is well distributed when SEM-EDX was applied. In addition, the volumetric properties of SMA also significantly improve with the addition of nano TiO2. It can be said that the addition of nano TiO2 is able to enhance the overall properties of bitumen.